Russia and Hungary: A dialogue of cultures in the space of literary texts: Book Review: Through "Alien" to "Own": Dialogue of Russian and Hungarian Cultures: Monograph / Edited by M.A. Lappo, V.V. Marosha. NGPU Publishing House, pp. 240. ISBN 978-00226-049-2, Novosibirsk, 2023 - Sedelnikova, Olga; Shatokhina, Anastasia (Slavica, 2024)
This monograph presents the results of a joint interdisciplinary project of Russian and Hungarian philologists to study the facts of interaction between Russian and Hungarian cultures in the space of literary texts. It examines various manifestations of the interaction of cultures: from the study of cases of direct influence to intertextual forms of assimilation and interpretation of elements of a foreign culture, current trends in translation reception. The volume includes papers by a wide range of authors whose texts made up the material of the study (from F.M. Dostoevsky and S. Veresh to E. Vodolazkin and Y. Berg).